2017
DOI: 10.1186/s12889-017-4850-2
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the relationships between sleep duration and health indicators in the early years (0–4 years)

Abstract: BackgroundThe objective of this systematic review was to examine for the first time the associations between sleep duration and a broad range of health indicators in children aged 0 to 4 years.MethodsElectronic databases were searched with no limits on date or study design. Included studies (published in English or French) were peer-reviewed and met the a priori determined population (apparently healthy children aged 1 month to 4.99 years), intervention/exposure/comparator (various sleep durations), and outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
235
2
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 306 publications
(261 citation statements)
references
References 91 publications
16
235
2
8
Order By: Relevance
“…Moreover, it has been suggested that the adverse effect of short sleep duration on adiposity may be moderate during early childhood, which is likely to manifest over time if the short sleep duration is prolonged. In that case, it may not be easily observed in a younger and healthier population like our sample . Since preschoolers who have short sleep duration may also sleep less in their toddlerhood and infancy, there may be stronger accumulative effects on adiposity, and it may be easier to find significant associations, compared with toddlers.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Moreover, it has been suggested that the adverse effect of short sleep duration on adiposity may be moderate during early childhood, which is likely to manifest over time if the short sleep duration is prolonged. In that case, it may not be easily observed in a younger and healthier population like our sample . Since preschoolers who have short sleep duration may also sleep less in their toddlerhood and infancy, there may be stronger accumulative effects on adiposity, and it may be easier to find significant associations, compared with toddlers.…”
Section: Discussionmentioning
confidence: 85%
“…A lack of adequate amount of sleep in school‐aged children and adolescents has been described to be one contributing factor to obesity . A recent systematic review in children under 5 years of age suggested that shorter sleep duration was associated with concurrent and later excess of adiposity in 20 (out of 31) studies . However, most of those studies focused on preschoolers (3‐5 years), whereas evidence in infancy and toddlerhood (prior to 3 years) is scarce and less consistent.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While multiple prior studies have demonstrated an increased risk of obesity with short sleep duration, this has not, to the best of our knowledge, been previously explored in AI children. While most prior studies examining this relationship have been performed in school‐aged children, a recent meta‐analysis including only children 0–4 years did find that 10 of 18 cross‐sectional and 10 of 13 longitudinal studies reported a significant association between shorter sleep duration and measures of adiposity . Importantly, sleep duration, obesity risk and their interaction may differ depending on culture.…”
Section: Introductionmentioning
confidence: 94%